From Knowledge to Technological Resonance: Systematic Literature Review - Fikrul Hakim (Digital Innovation : International Journal of Management, 2026)
Rapid technological change in the digital era has reshaped the nature of organizational innovation, requiring firms not only to innovate but also to align their innovation activities with technological developments and market dynamics, a capability referred to as Techno-Resonance Innovation Capability (TRIC). Although Knowledge Management (KM) has been widely recognized as a driver of innovation, studies that explicitly link KM to the development of techno-resonant innovation remain limited. This study aims to address this gap by systematically reviewing the literature to examine how KM contributes to innovation capability and how this relationship evolves toward TRIC through absorptive capacity. Using the systematic literature review methodology proposed by Tranfield et al., this study follows three stages planning, conducting, and reporting the review to identify, evaluate, and synthesize relevant studies on KM, absorptive capacity, innovation capability, and techno-resonance. The findings indicate that innovation capability emerges from interconnected KM processes, including knowledge acquisition, sharing, storage, and application, which form the organizational infrastructure for innovation. Absorptive capacity is identified as a key bridging mechanism that enables organizations to transform managed knowledge into innovative outcomes by enhancing their ability to acquire, assimilate, transform, and exploit technological knowledge. This study concludes that integrating KM and TRIC through absorptive capacity extends conventional innovation capability models and provides a stronger theoretical explanation of innovation in technology-driven and digitally dynamic environments.